Emploi des « seniors » et conditions de travail : une étude statistique comparative entre pays d’Europe - Céline Mardon; Serge Volkoff (Perspectives Interdisciplinaires sur le Travail et la Santé)
Employment rates of ageing workforce have become a major concern, in particular for international organisms. In this article we analyze the links between work constraints and employment of elderly, by comparing various European countries. Ergonomic and demographic methodologies are being called on. Local studies and statistical approaches actually emphasize difficulties, especially perceived by elderly workers, in relation with four main types of constraints : painful positions, shift work, high time pressure, and fast paced changes in techniques or organisation. For each of these characteristics, we first recap why it is tricky for elderly, then we study its relations with seniors’ employment rate in 25 countries, using the ESWC data (European Survey on Working Conditions). Our results suggest that « high performance » countries in terms of senior employment have, better than others, mastered or adapted these characteristics, in particular by lowering physical efforts, and by promoting lifelong learning.